DESENVOLVIMENTO DE METODOLOGIA DE ANÁLISE DA REATIVIDADE DO CARVÃO VEGETAL - Fonseca, Paulo Ricardo Fraga (2020)
Although steel is one of the most used materials in the world and the steel sector moves the world economy, there is an obstacle that is the lack of standardization of charcoal. The lack of this reactivity parameter makes this one of the major obstacles t